Investing in Euro equity markets through Parametric Portfolio Policies (PPP) : a feasibility analysis of the PPP approach on principal euro-zone stock markets - Zanello, Federico (2022)
In this paper we exploit the parametric portfolio policy (PPP) approach proposed by Brandt, Santa Clara and Valkanov (2009) on an investable set of only large European stocks, with the goal of accepting its advantages to the portfolio’s optimization problem also in the Euro financial markets. Our sample includes all the euro-denominated equities that have been listed between January 1990 and December 2019 on the stock exchange of one of four large European countries: France, Germany, Italy and Spain. The optimal portfolio’s weights are determined by a function that considers three stock-specific characteristics: the market capitalization of the company, its book-to-market ratio and its recent 12-month lagged return. The coefficients of this function, corresponding to size, value and momentum, respectively, are established by optimizing the investor’s average utility of the portfolio’s return over the sample period. We test the model both in-sample and out-of-sample and benchmark the results against the equalweighted and value weighted portfolios. Also, we extend the base case by including short sales constraints and a sensibility analysis to different coefficients of risk aversion. Overall, we confirm the parametric optimization’s improvements to asset-allocation. The optimal portfolios generate robust performances, in-sample and out-of-sample, which are consistently superior to both benchmarks’ figures. However, this methodology presents a limitation to its practical use: the large trading activity required. From the coefficients’ estimation, we establish that the European investor always prefers value stocks and past winners, while the size preference depends on the risk’s tolerance.